Kajian Upaya Preventif Kepala Sekolah dan Kepolisian dalam Mencegah Tindak Penculikan Anak: Studi Kasus di SDN Kanigaran 6 Probolinggo - dwi wahyuni; mohammad hendra; khusnul hitaminah; hasan basri (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The high vulnerability of children to kidnapping, particularly after school, as occurred at SDN Kanigaran 6 Probolinggo, is a crucial concern in child protection efforts. The discussion shows that preventive measures include student supervision, a pick-up system, access restrictions, CCTV installation and police outreach. However, obstacles include limited supervisory staff, low parental discipline and a lack of supporting facilities. It can be concluded that effective child kidnapping prevention requires strong collaboration between schools, the police, parents and the community to create a safe environment for children